Relationships between daily physical activity combinations and psychophysical health status of Italian breast cancer survivors. Issue 3 (3rd July 2022) - Di Blasio, Andrea; Di Dalmazi, Giulia; Morano, Teresa; Bucci, Ines; Verrocchio, Sara; Grossi, Simona; Cianchetti, Ettore; Valentini, Pasquale; Cugusi, Lucia; Gobbo, Stefano; Bergamin, Marco; Grassadonia, Antonino; et al.
ABSTRACT: In breast cancer survivors (BCS), the contemporaneous increase of sedentary time and reduction of physical activity (PA) requires early attention because it has negative consequences for their health. Aims of the study were to investigate: a) the correlations between PA, sedentarism, and health-related measures; b) the association between different patterns of daily activity and health-related outcomes. Two hundred and nineteen BCS (50.98 ± 6.28) were selected for this study. Psychological, anthropometric, endocrine, sleeping, and both daily sedentary time and PA variables were considered. Sedentarism and PA have opposite correlations with anthropometric variables, anxiety, depression, morning salivary cortisol, and sleeping characteristics. The first favors pathological values and the latter favors normal values. Regression tree analysis showed the impact of different daily sedentary time and PA combinations on the investigated variables and allowed the individualization of their optimal combination for health. Our results could be useful to healthcare providers and BCS.